Ideology and Specific Support for the Supreme Court. (December 2021) - Haglin, Kathryn; Jordan, Soren; Merrill, Alison Higgins; Ura, Joseph Daniel
We develop and assess an account of ideological asymmetries in public support for the Supreme Court. We find that specific support for the Supreme Court is more strongly negatively related to perceptions that the Court is overly liberal than perceptions that the Court is overly conservative. Our findings provide a more complete theoretical account of dynamics in specific support for the Supreme Court and indicate a mechanism behind the recent decline in the Supreme Court's public standing.